# |
ODE |
Mathematica |
Maple |
\[
{}y^{\prime \prime }+5 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}8 y^{\prime \prime }+6 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+21 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}7 y^{\prime \prime }+4 y^{\prime }-3 y = 0
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+9 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}3 y^{\prime \prime }-y^{\prime } = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-12 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+12 y = 0
\] |
✓ |
✓ |
|
\[
{}2 y^{\prime \prime }-7 y^{\prime }-4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+10 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+36 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+100 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-y = 0
\] |
✓ |
✓ |
|
\[
{}6 y^{\prime \prime }+5 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}9 y^{\prime \prime }+6 y^{\prime }+y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+20 y = 0
\] |
✓ |
✓ |
|
\[
{}a y^{\prime \prime }+2 b y^{\prime }+c y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+2 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-16 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+5 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+3 y = 0
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = 8 \,{\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = -{\mathrm e}^{-9 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+3 y = 2 \,{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 2 t -4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+y = t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime } = 3-4 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y = \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 4 \cos \left (t \right )-\sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \cos \left (2 t \right )+t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 3 t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = 3 t^{4}-2 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }+13 y = 2 t \,{\mathrm e}^{-2 t} \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = -1
\] |
✓ |
✓ |
|
\[
{}5 y^{\prime \prime }+y^{\prime }-4 y = -3
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }-8 y = 32 t
\] |
✓ |
✓ |
|
\[
{}16 y^{\prime \prime }-8 y^{\prime }-15 y = 75 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+26 y = -338 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime }-4 y = -32 t^{2}
\] |
✓ |
✓ |
|
\[
{}8 y^{\prime \prime }+6 y^{\prime }+y = 5 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+8 y = -256 t^{3}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime } = 52 \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-6 y^{\prime }+13 y = 25 \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-9 y = 54 t \sin \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-5 y^{\prime }+6 y = -78 \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+4 y = -32 t^{2} \cos \left (2 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime }-20 y = -2 \,{\mathrm e}^{t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y^{\prime }-5 y = -648 t^{2} {\mathrm e}^{5 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+12 y = -2 t^{3} {\mathrm e}^{4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = 8 \,{\mathrm e}^{4 t}-4 \,{\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = t^{2}-{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = -24 t -6-4 t \,{\mathrm e}^{-4 t}+{\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = t^{2}-{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime } = t^{2}+{\mathrm e}^{t}+\sin \left (t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+3 y^{\prime } = 18
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y = 4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-4 y = 32 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }-3 y = -2
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-6 y = 3 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+8 y^{\prime }+16 y = 4
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+7 y^{\prime }+10 y = t \,{\mathrm e}^{-t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+25 y = -1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = -{\mathrm e}^{3 t}-2 t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-y^{\prime } = -3 t -4 t^{2} {\mathrm e}^{2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime } = 2 t^{2}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime } = -24 t -6-4 t \,{\mathrm e}^{-4 t}+{\mathrm e}^{-4 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-3 y^{\prime } = {\mathrm e}^{-3 t}-{\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 y = \left \{\begin {array}{cc} 2 t & 0\le t <\pi \\ 0 & \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+9 \pi ^{2} y = \left \{\begin {array}{cc} 2 t & 0\le t <\pi \\ -2 \pi +2 t & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = \left \{\begin {array}{cc} 0 & 0\le t <\pi \\ 10 & \pi \le t <2 \pi \\ 0 & 2 \pi \le t \end {array}\right .
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+y^{\prime }-2 y = f \left (t \right )
\] |
✓ |
✓ |
|
\[
{}x^{\prime \prime }+9 x = \sin \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}4 y^{\prime \prime }+4 y^{\prime }+37 y = \cos \left (3 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y = 1
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y^{\prime } = t
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-7 y^{\prime }+10 y = {\mathrm e}^{3 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = 2 \cos \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+4 y^{\prime }+20 y = 2 t \,{\mathrm e}^{-2 t}
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+\frac {y}{4} = \sec \left (\frac {t}{2}\right )+\csc \left (\frac {t}{2}\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = \csc \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+16 y = \cot \left (4 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+2 y^{\prime }+50 y = {\mathrm e}^{-t} \csc \left (7 t \right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+6 y^{\prime }+25 y = {\mathrm e}^{-3 t} \left (\sec \left (4 t \right )+\csc \left (4 t \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }-2 y^{\prime }+26 y = {\mathrm e}^{t} \left (\sec \left (5 t \right )+\csc \left (5 t \right )\right )
\] |
✓ |
✓ |
|
\[
{}y^{\prime \prime }+12 y^{\prime }+37 y = {\mathrm e}^{-6 t} \csc \left (t \right )
\] |
✓ |
✓ |
|